The role of paper embedded security features in effective border control - Mansour, Saleh; Rohatgi, Shipra (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Security documents are crucial types of documents, whose authenticity is genuineand cannot be counterfeited. For different types of security documents, a security paperis used, which possesses the property of being impenetrable to mileage, high temperature with unequivocal GSM, haziness, and thickness. This makes it sensible for merging the security features that make it different from normal paper. The commonly used substrate for any security document manufacturing is either plastic or paper. The processof manufacturing a security document begins with paper manufacturing by mechanicaland chemical processing of wood pulp, and the security elements are incorporated in the further processing stages. The raw material used is mainly pure cotton fiber-based cellulose mixed with titanium oxide. The major security features include security threads, fibers, planchettes, and water marks which play a critical role in keeping up the uprightness of the security record for a fruitful edge control. Identity theft as well as deceitfulutilization of personality and travel reports are the fundamental dangers confronting the control at international borders, while checking the legitimacy of the travelers’ character records assumes an essential job in guaranteeing the effectiveness of fringe control.
Keywords: substrate; security paper; watermark; fibers; planchettes; hi-lights; security thread